Cosmogenic Radionuclides In Ice Cores From West Antarctica - Chen, Zhijie; Woodruff, Thomas Edward; Caffee, Marc W (Purdue University, 2014)
Cosmogenic nuclides such as 10Be and 26Al are formed in the atmosphere by cosmic rays and come down to the ground through snow which became ice in Antarctica. The concentrations of 10Be and 26Al in ice cores can reveal important information about climate change, solar activity and geomagnetic change in the past. They can also be used to date very old ice. Since there is very little 26Al in the ice, its actual concentration is poorly known and the measured results don’t agree with each other. My research is focused on the measurement of the concentration of 26Al as well as 10Be in an ice core from Antarctica. The ice samples undergo several chemical and physical processes to be ready for measurement. Some key process includes separating different ions using ion chromatography, oxidizing the samples at high temperature, and loading the final sample holders. Finally the samples are measured by accelerator mass spectrometry (AMS). After the AMS measurement, we calculated the average concentrations of 10Be for our sample to be 40,000 atoms g-1 and the concentration for 26Al is around 76 atoms g-1. The average ratio of 26Al/10Be is 2.40 * 10-3. This study will contribute to our knowledge of using 26Al/10Be to date very old ice. Combined with other similar studies at different ice core depths, we can also have a full picture of the change of concentration of cosmogenic nuclides through time.